Competitiveness and technological gap - a comparative analysis between Brazil and selected European countries - Melo, Tatiana Massaroli [UNESP]; Correa, Andre Luiz [UNESP]; Carvalho, Eneas Goncalves [UNESP]; Possas, Mario Luiz [UNESP] (Univ Estadual Campinas, Inst Geociencias, Dept Politica Cientifica & Tecn, 2017)
This paper analyzes the innovative behavior patterns of different countries in order to verify the existence of a technological gap between Brazil and the technologically most dynamic countries in the sample, which will be called technological frontier. The proposed methodology consists of correspondence analysis, performed from a set of innovation indicators based on Technological Innovation Survey (PINTEC) IBGE and the Community Innovation Survey (CIS). Based on four sectoral innovation indicators built for Brazil and a set of ten European countries, correspondence analysis was prepared considering the following dimensions: (i) country-indicator; (ii) industry-indicator.
Keywords: Technological Capabilities; Competitiveness; Technological Gap; Innovation Indicators